2016
DOI: 10.1503/cjs.013315
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of gastric bypass, sleeve gastrectomy and adjustable gastric banding in a population-based bariatric program: prospective cohort study

Abstract: Background: Bariatric surgery in Canada is primarily delivered within publicly funded specialty clinics. Previous studies have demonstrated that bariatric surgery is superior to intensive medical management for reduction of weight and obesity-related comorbidities. Our objective was to compare the effectiveness and safety of laparoscopic Roux-en-Y gastric bypass (RYGB), sleeve gastrectomy (LSG) and adjustable gastric banding (LAGB) in a publicly funded, population-based bariatric treatment program. Methods:We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…For example, complications observed in the STAMPEDE Trial of gastric bypass and sleeve gastrectomy compared to medical therapy for the treatment of diabetes through 3 years included intra-abdominal bleeding (and subsequent need for transfusion), gastrointestinal leak, bowel obstruction, dehydration requiring intravenous treatment, stricture, ulcers, and ketoacidosis [12, 13]. Weight loss with vBloc was shown to be similar to that reported for laparoscopic adjustable gastric banding (LAGB) in a 2-year report comparing bypass, sleeve, and LAGB where the completed case evaluation showed 6 ± 8.2 % TWL with LAGB compared to 8 ± 9.5 % TWL with vBloc [14]. …”
Section: Discussionmentioning
confidence: 71%
“…For example, complications observed in the STAMPEDE Trial of gastric bypass and sleeve gastrectomy compared to medical therapy for the treatment of diabetes through 3 years included intra-abdominal bleeding (and subsequent need for transfusion), gastrointestinal leak, bowel obstruction, dehydration requiring intravenous treatment, stricture, ulcers, and ketoacidosis [12, 13]. Weight loss with vBloc was shown to be similar to that reported for laparoscopic adjustable gastric banding (LAGB) in a 2-year report comparing bypass, sleeve, and LAGB where the completed case evaluation showed 6 ± 8.2 % TWL with LAGB compared to 8 ± 9.5 % TWL with vBloc [14]. …”
Section: Discussionmentioning
confidence: 71%
“…Proportion meta-analysis of randomized and observational studies found a pooled incidence of 20% (95% CI 13% to 26%, df = 10, I 2 = 89%) for complications requiring surgical intervention, 2% (95% CI 1% to 3%, df = 7, I 2 = 0%) for band erosion, 7% (95% CI 4% to 10%, df = 9, I 2 = 72%) for band removal, 4% (95% CI 3% to 5%, df = 6, I 2 = 0) for port revision, and 19% (95% CI 12 to 26%, df = 8, I 2 = 85%) for overall complications [77][78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: Justificationmentioning
confidence: 99%
“…(14) but disagrees with study in America by. (15) Most of nurses don't have good knowledge about gastrectomy because this operation is considered new method in Iraq to decrease the weight and most of nurses don't read about this operation in there study program, that is mean all of nurses equal to have bad knowledge, for this reason association cannot be found between overall assessment of nurses knowledge about sleeve gastrectomy and their demographic data between overall assessment of nurses knowledge about sleeve gastrostomy and their demographic data, this result agree with Hameed (2006), he pointed no significant correlation between overall assessment of nurses' knowledge and their demographic data (16)…”
Section: Cont Table (4): Correlation Between Overall Assessment Of Nurses' Knowledge and Socio-demographic Characteristicsmentioning
confidence: 99%